Analisis Kedaruratan K3 dengan Kejadian Kecelakaan pada Proyek Konstruksi Bangunan di Perumahan Grand Safira Binjai - Adinda, Adinda (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Every construction project must pay attention to occupational safety and health (K3), especially in residential areas where building work is taking place. Workplace accidents are a major problem that can directly harm employees, the environment, and the project as a whole. Therefore, K3 emergency analysis is very important to find possible accidents and choose the best mitigation measures. The aim of this research is to identify K3 emergencies related to construction accidents at the Grand Safira Binjai housing complex. Before and after tests were carried out as part of the quasi-experimental writing technique to measure the effectiveness of the research conducted and to provide guidance. The research results showed that workers' knowledge of the work environment increased from 57.2% to 94.4% and knowledge of the use of personal protective equipment (PPE) increased from 39.8% to 85.2% due to K3 emergencies with accidents in buildings. construction project at the Grand Safira Binjai housing complex. This aims to increase workers' awareness and knowledge regarding Occupational Safety and Health (K3), create a safer workplace, increase productivity, and reduce costs related to work-related accidents and illnesses.